2022
DOI: 10.21608/ajar.2022.266486
|View full text |Cite
|
Sign up to set email alerts
|

Using the natural zeolite (clinoptiolite) in removing ammonia, heavy metals and improving water quality in fish ponds

Abstract: The progressive build-up of toxic wastes, such as ammonia and heavy metals, is a problem of intensive fish culture systems. . This study was conducted to determine the effects of the natural zeolite (clinoptiolite) in removing ammonia and heavy metals. Twelve cement ponds (each 2m 3 ) were used to carry out three experimental zeolite treatments with the following concentrations: 1kg/1000L, 2kg/1000L, and 3kg /1000L ( with three replications, in addition to 0 concentration for the control. The clinoptilolite wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…In a study conducted by Hamed et al (57), natural zeolite was used to remove heavy metals from the wastewater of a fish farm. The results showed that zeolite was able to effectively remove heavy metals, including Cu, Zn, and Pb, from the wastewater.…”
Section: Zeolitementioning
confidence: 99%
“…In a study conducted by Hamed et al (57), natural zeolite was used to remove heavy metals from the wastewater of a fish farm. The results showed that zeolite was able to effectively remove heavy metals, including Cu, Zn, and Pb, from the wastewater.…”
Section: Zeolitementioning
confidence: 99%
“…The provided area for aquaculture growth, the scarcity of freshwater, and the restrictive wastewater rules are the main hindrances to long-lasting conventional systems [13,14]. In order to establish a sustainable sector for dessert aquaculture, several studies have examined ways to improve subterranean seawater quality via the use of different technologies, including activated carbon [15,16], probiotic and biofloc technology system [17,18], biological and sand filters [19][20][21], and zeolites [22][23][24][25]. Fish are near the top of the marine food chain, so heavy metals can usually get into their bodies from food, water, and sediments [26][27][28].…”
Section: Introductionmentioning
confidence: 99%